Adjuvant External Radiation Impacts Outcome of Pelvis-limited Stage III Endometrial Carcinoma: A Multi-institutional Study. (August 2018) - Albuquerque, Kevin; Folkert, Michael; Mayadev, Jyoti; Christie, Alana; Liotta, Margaret R.; Nagel, Christa; Sevak, Parag; Harkenrider, Matthew M.; Lea, Jayanthi S.; Hanna, Rabbie K.; Small, William C.; Miller, David S.; et al.
Abstract : Background: Adjuvant therapy choice for women with FIGO stage III endometrial carcinoma (EC) is controversial. We investigate the comparative benefit of adjuvant chemotherapy (CT) alone, radiation therapy alone (RT) or in combination (chemotherapy and radiation therapy [CRT]) with respect to recurrence-free survival (RFS) and overall survival (OS) in women with pelvis-limited (PL) EC (stage IIIA, IIIB, and IIIC1). Materials and Methods: A multi-institutional database of 270 surgically staged women with PLEC was analyzed. Univariate log-rank analyses and Cox regression multivariate analyses (MVA) were performed to identify factors associated with RFS and OS. Results: Median RFS and OS were 112 and 130 months, respectively, for the full cohort. Adjuvant treatment was CT in 21%, RT in 27%, and CRT in 47%. Age, year of treatment, grade, histology, and adjuvant treatment were significantly associated with RFS and OS on univariate analysis. PLEC patients receiving CT alone fared worse in terms of RFS ( P= 0.07 relative to RT and <0.01 relative to CRT). On MVA, CRT retained significantly improved RFS relative to CT (hazard ratio for recurrence 0.38, P< 0.01). PLEC patients receiving RT or CRT had improved OS compared with CT, P< 0.01 and 0.03, respectively. On MVA, both RT only and CRT retained association with improved OS relative to CT alone (hazard ratio for death, 0.43, P =0.02 and 0.40, P< 0.01, respectively). Conclusions: For surgically staged PL stage III EC, treatment regimens incorporating RT were associated with improved survival endpoints relative to CT alone. As such, RT should be considered an important component in the adjuvant management of stage III PLEC. Abstract : Supplemental Digital Content is available in the text.